Robot Beroda Pendeteksi Gas Karbon Monoksida dan Metana Berbasis IoT Menggunakan Metode Finite State Machine dan Fuzzy Logic - Wira Adi Winata; Khairul Anam; Ali Rizal Chaidir (Jurnal Rekayasa Elektrika, 2022)
Occupational Safety and Health (K3) is an important requirement needed in mining. This is because activities in mining have great risks and are associated with unpredictable natural conditions. One of them is the leakage of hazardous gas at the mine site caused by mining activities. This article proposes a wheeled robot to detect carbon monoxide gas and methane gas based on the Internet of Things (IoT) using Finite State Machine (FSM) and Fuzzy Logic. The finite state machine (FSM) in this study is used as a control of the robot’s movement, while fuzzy logic is used as a safety classification of the readable state of dangerous gases. The results showed that the system was capable of detecting gas and the information is successfully sent to a web server. In addition, the use of lidar can detect obstacles around the robot.